2021
DOI: 10.1055/s-0041-1722841
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4-Related Disease Masquerading an Epidural Spinal Cord Tumor

Abstract: Background Immunoglobulin G4–related disease (IgG4-RD) is a recently identified multisystemic fibroinflammatory condition of unclear etiology. IgG4-RD of the epidural tissue causing spinal cord compression is extremely rare. Case description Here, we present a 27-year-old male with epidural mass, causing spinal cord compression at the level of D5-D6. The mass proved pathologically to be epidural inflammatory pseudotumor (IPT) related to IgG4. Spinal decompression was done. The patient was started on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The research by Ferreira et al (11) showed that plasmacytosis was first detected in biopsy of inflammatory pseudotumor, with more than 50% IgG4-positive plasma cells in the thoracic spine. We used the PubMed database to identify seven cases (2016-2020) of IgG4-RD IPT (5)(6)(7)(8)(9)(10)(11). In these cases, the mean age of the patients was 44.5 years, with the majority being male.…”
Section: Discussionmentioning
confidence: 99%
“…The research by Ferreira et al (11) showed that plasmacytosis was first detected in biopsy of inflammatory pseudotumor, with more than 50% IgG4-positive plasma cells in the thoracic spine. We used the PubMed database to identify seven cases (2016-2020) of IgG4-RD IPT (5)(6)(7)(8)(9)(10)(11). In these cases, the mean age of the patients was 44.5 years, with the majority being male.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin (Ig)G4-related disease belongs to a rare compilation of conditions in rheumatology, its varied manifestation make it a diagnostic challenge among other lesions which more frequently present as mass lesions [ 1 ]. The multitude of organs that are affected in IgG4-related disease commonly includes salivary glands, pancreas, liver, lungs, heart, and kidney [ 2 , 3 ]. However, the facade of central nervous system (CNS) manifestations in IgG4-related disease makes them mystifying and is less documented [ 4 ].…”
Section: Introductionmentioning
confidence: 99%